EFFORTS TO INCREASE THROUGH SELF EFFICACY WITH COUNSELING SERVICES TECHNICAL SELF MANAGEMENT TO CONVICTED CRIMINAL IN JAIL II B CLASS LABUHAN DELI 2018 - Gusman Lesmana (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2019)
Prisoners have considered themselves to be a group that is considered dangerous and who consider themselves to have a large disability and are considered low in society. Therefore, there needs to be an effort to improve the prisoners' self-efficacy to improve their motivation in interacting and interacting with other normal communities when they join later in society by using relevant methods namely self management with indicators of development at the stage of self-monitoring or self-observation , self-evaluation and then self-improvement. The phenomenon of rejection of the presence of prisoners has sounded very common. This has a major impact on the survival of prisoners after being released from prison sentences. This study aims to improve the self efficacy of individual ex-prisoners in the Labuhan Deli Class IIB Detention Center using the services of Guidance and Counseling self management techniques. The subject of this study amounted to 85 people, namely inmates in the Labuhan Deli Class IIB Detention Center with a detention period of 6 months down to be free. Self management techniques are forming and changing desired behavior through three stages. The results of the study show that self management techniques are effective in increasing prisoners' self-efficacy to interact with the general public. This research was conducted to explain the quantitative relation between service of counseling technique of Self Management with Self efficacyof convict. The results of the research conclude that the state of Self efficacyof convict community members is at a low level due to the strong rejection from the community towards the convict community. The results and conclusion to answer the positive hypothesis is (r count> r table), so, thus (0.915> 0.304) The analysis process of SPSS from the questionnaire of the research respondents is 40 prisoners sample of 0.915 which means 91.5% with sig. 0,000 the magnitude of the influence of the application of self-management technique counseling to prisoners' self-efficacy.